Cancer case trends following the onset of the COVID‐19 pandemic: A community‐based observational study with extended follow‐up. Issue 7 (17th December 2021) - Drescher, Charles W.; Bograd, Adam J.; Chang, Shu‐Ching; Weerasinghe, Roshanthi K.; Vita, Ann; Bell, R. Bryan
Abstract : Background: The coronavirus disease 2019 (COVID‐19) pandemic has impacted health care delivery worldwide. Cancer is a leading cause of death, and the impact of the pandemic on cancer diagnoses is an important public health concern. Methods: This cross‐sectional study retrospectively analyzed the electronic medical records of 80, 138 cancer patients diagnosed between January 1, 2019, and May 31, 2021. Outcome measures included weekly number of new cancer cases and trends in weekly cancer cases, before and after the pandemic; patient demographics; and positive COVID‐19 test rates. Results: Beginning March 4, 2020, defined as the onset of the pandemic, weekly cancer cases declined precipitously (–110.0 cases per week [95% confidence interval, −190.2 to −29.8]) for 4 weeks, followed by a moderate recovery (+23.7 cases per week [9.1 to 38.4]) of 10 weeks duration. Thereafter, weekly cancer cases trended slowly back toward pre‐COVID‐19 baseline levels. Following the pandemic onset, there was a cumulative year‐over‐year decline in cancer cases overall of 7.3%, including a 20.2%, 14.3%, and 12.8% decline in nonmelanoma skin cancer, breast cancer, and prostate cancer, respectively. Changes in case volumes were accompanied by variations in patient characteristics, including region, age, gender, race, insurance coverage, and COVID‐19 positive test rates ( P < .01 for all). Among patients tested for COVID‐19, 5.3% had a positive result. Conclusions: The data in this study demonstrate a substantial reduction in cancer diagnoses following the onset of COVID‐19, which appear to reach expected pre‐COVID norms 12 months later. The largest reduction was noted among cancers that are typically screen‐detected or identified as part of a routine wellness examination. Abstract : The data in this study demonstrate a substantial reduction in cancer diagnoses following the onset of COVID‐19, which appear to have reached expected pre‐COVID norms roughly 1 year after the onset of the pandemic.